Performance comparisons of the kicking of stationary and rolling balls in a futsal context - Barbieri, Fabio A. [UNESP]; Gobbi, Lilian T. B. [UNESP]; Santiago, Paulo R. P.; Cunha, Sergio A. (Routledge Journals, Taylor & Francis Ltd, 2010)
Angular kinematics of the hip, knee, and ankle joints, as well as ball velocity and accuracy for stationary and rolling balls were compared in a futsal (Five-a-Side Indoor soccer) context. Ten futsal athletes performed five kicks each on stationary and rolling futsal balls. Six digital cameras (120Hz) recorded the kicks. For both kick types, angles for hip, knee, and ankle joints were calculated using Euler angle conventions. Angular velocity, ball velocity, foot linear velocity, relative velocity, and accuracy also were analyzed. The kicking of both stationary and rolling balls showed similarities for ball velocity (24.2 +/- 2.2m/s and 23.8 +/- 2.7m/s, respectively), foot velocity (17.6 +/- 1.8m/s and 17.2 +/- 2.2m/s, respectively), and accuracy (26% and 24% target hits, respectively). We observed few differences in angular kinematics and angular joint velocities between kick types. Elite players can make online adjustments in the preparatory phase so that kicking a rolling ball is almost exactly like kicking a stationary ball.
Keywords: Angular kinematics; futsal; kicking a rolling ball; performance